Third voice in a criminal justice system: the voice of the victim through victim impact statement - Sidhu, Baljit Singh; Shair Mohamed, Mohd. Akram (The Malaysian Current Law Journal Sdn Bhd, 2015)
Only two voices heard in a criminal justice: that of the State and that of the accused person. The victim's voice is only an accessory in order to secure a conviction against the accused. Victim Impact Statement (VISs) were introduced in Malaysia vide the Criminal Procedure Code (Amendment) Act 2010 and are intended to allow victims or a member of his family to express how a particular crime has affected them. VISs could encompass various aspects such as physical or psychological damage, financial costs as well as opinions on the appropriate sentencing that should be given to the offender. Whilst VISs are surely welcomed to the Malaysian legal scene, are they fulfilling their intended purposes in light of the obvious failings in their implementation, including the lack of guidelines as well as the failure to bring the Child Act 2001 in line with the introduction of VISs only through the general procedural law ie, the CPC?